2021
DOI: 10.1186/s40104-020-00522-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of lactose in weanling pig nutrition: a literature and meta-analysis review

Abstract: Lactose plays a crucial role in the growth performance of pigs at weaning because it is a palatable and easily digestible energy source that eases the transition from milk to solid feed. However, the digestibility of lactose declines after weaning due to a reduction in endogenous lactase activity in piglets. As a result, some lactose may be fermented in the gastrointestinal tract of pigs. Fermentation of lactose by intestinal microbiota yields lactic acid and volatile fatty acids, which may positively regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 85 publications
0
20
0
Order By: Relevance
“…The lack of differences in fecal score or diarrhea frequency between pigs fed diets with adequate or deficient concentrations of Ca and P reflects the results from stomach pH and further indicates that a reduction in dietary Ca and P failed to change gastric and intestinal conditions. It is possible that this observation is a result of the fact that phase 1 diets used in this experiment contained 15% lactose, which may have resulted in production of lactic acid from microbial fermentation ( Suiryanrayna and Ramana, 2015 ), and therefore, reduced stomach pH, as has been recently reported ( Zhao et al, 2021 ). If that was the case, lactic acid production could have reduced the possibility for a further reduction in gastric pH by reducing Ca and P in the diet.…”
Section: Discussionmentioning
confidence: 69%
“…The lack of differences in fecal score or diarrhea frequency between pigs fed diets with adequate or deficient concentrations of Ca and P reflects the results from stomach pH and further indicates that a reduction in dietary Ca and P failed to change gastric and intestinal conditions. It is possible that this observation is a result of the fact that phase 1 diets used in this experiment contained 15% lactose, which may have resulted in production of lactic acid from microbial fermentation ( Suiryanrayna and Ramana, 2015 ), and therefore, reduced stomach pH, as has been recently reported ( Zhao et al, 2021 ). If that was the case, lactic acid production could have reduced the possibility for a further reduction in gastric pH by reducing Ca and P in the diet.…”
Section: Discussionmentioning
confidence: 69%
“…Tran et al showed that a high concentration of dietary lactose (20%) increased the relative abundance of Lactobacilli and reduced E. coli in the large intestine of piglets ( Tran et al, 2012 ). Furthermore, lactose feeding increases the proportions of fecal Lactobacilli and Bifidobacteria in lactose maldigesters ( Szilagyi et al, 2010 ; Ito and Kimura, 1993 ), which are considered to be colonic microbes adapting to the presence of lactose in the colonic lumen ( Forsgård, 2019 ; Zhao et al, 2021 ). In our study, we found the similar results that included the relative abundance of Lactobacillus and Bifidobacterium being significantly increased in the HLD group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, 15 to 20% lactose is included in the phase 1 diet of pigs weaned at approximately 3 wk of age and fed for 7 d, followed by a phase 2 diet containing 10% to 15% lactose for the subsequent 7 to perhaps 14 d. There appeared to be almost no limit to the pig’s response to increasing levels of lactose during the first week after weaning. Interestingly, the presence of antibiotic growth promotants in the diet muted the lactose response ( Zhao et al, 2021 ). Beyond phase 2, lactose is rarely recommended, unless the feed is being directed to pigs with compromised health or performance, or are lighter in weight than normal.…”
Section: Dietary Approaches To Improve Abf Productionmentioning
confidence: 99%
“…Furthermore, researchers have investigated alternative carbohydrates with interesting results. Dextrose, sucrose, liquid lactose and molasses have all been proposed as full or partial replacements for dried lactose ( Dunmire et al, 2020 ; Zhao et al, 2021 ). Recently, Clouard et al (2018) reported that using maltodextrin in place of lactose in a liquid milk replacer improved cognitive performance 8 wk later and did not impact growth performance.…”
Section: Dietary Approaches To Improve Abf Productionmentioning
confidence: 99%